Model Reference Adaptive Control Based on Lyapunov Stability Theory - Minan TANG; Xiaoming WANG; Jie CAO; Ying LI (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to the obvious characteristics of time-varying nonlinear controlled object, in order to improve the control performance, can use appropriate adaptive control strategy. Based on the research object system of a certain amount of input to control variables, according to Lyapunov stability theory, the research object system input/output variable a model reference adaptive control system was design. And after analysis the method to improve the system starting stage characteristics, dynamic process performance and system anti-interference and resistance to process parameters is presented. Simulation and research results show that the proposed control method is effective DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4450